2011
DOI: 10.1002/hed.21790
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck paragangliomas: Report of 175 patients (1989–2010)

Abstract: Multifocal occurrence, potential malignancy, genetic aspects, possible coincidence of thyroid carcinoma, and hormone production have to be considered in patients with head and neck PGLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 24 publications
7
86
0
Order By: Relevance
“…2) (34,35). One year later, she presented with bilateral PCCs and an intra-abdominal extra-adrenal (ea) PGL and was subsequently shown to harbor a heterozygous germline SDHD mutation c.14GOA (p.Trp5X).…”
Section: Case Seriesmentioning
confidence: 99%
“…2) (34,35). One year later, she presented with bilateral PCCs and an intra-abdominal extra-adrenal (ea) PGL and was subsequently shown to harbor a heterozygous germline SDHD mutation c.14GOA (p.Trp5X).…”
Section: Case Seriesmentioning
confidence: 99%
“…5, 12 Papaspyrou et al did report one case of their 175 patient series in which the patient was found to be positive for a mutation in the SDHC gene after presenting with multiple malignant PGLs of the ITF, carotid body, and jugulotympanic region. 5 Although this observation is certainly interesting, a large amount of additional data are needed before any specific conclusions on the topic can be made.…”
Section: Discussionmentioning
confidence: 95%
“…There is also a well-established familial association that has been observed in upward of 10% of PGLs, owing predominantly to mutations in three of the four succinate dehydrogenase subunit genes (SDHB, SDHC, and SDHD). 1,5 This genetic predisposition carries an increased risk for multifocal tumor development, with an 80% chance of multicentricity in familial cases as opposed to only a 10 to 20% chance in sporadic cases. 1,5 The genetic characteristics of familial PGLs have been well described in various publications, such as Martin et al 2007 and Papaspyrou et al 2011, although SDHD is the most commonly implicated gene in the development of benign familial PGLs of the head and neck, and SDHB mutations have the highest rate of developing malignant PGLs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations